2017
DOI: 10.4103/jpn.jpn_162_16
|View full text |Cite
|
Sign up to set email alerts
|

Solitary intramedullary cervical cysticercosis without neurological deficit: A rare case report

Abstract: Neurocysticercosis is commonly seen intracranially and its incidence in the spinal cord is very low. Among spine dorsal region is more common due to more blood flow in this region and it is usually associated with lesion at other sites. The intramedullary location is rarer than extramedullary. Hence, solitary intramedullary cervical spine cysticercosis (ICC) is extremely rare entity. Only a handful numbers of cases are reported in the literature. All reported cases are presented with the neurological deficit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In only 12 of the cases of IM-NCC, antibodies were detected by various techniques, including enzyme-linked immunosorbent assay (ELISA), Western blot, and enzyme-linked immunoelectrotransfer blot (EITB). 24,25 In the review, it was concluded that surgery was the main modality of treatment (n ¼ 29), while 16 patients were managed medically with anticysticercal agents (albendazole, praziquantel). One of the patients refused any treatment.…”
Section: Review Of Literature and Resultsmentioning
confidence: 99%
“…In only 12 of the cases of IM-NCC, antibodies were detected by various techniques, including enzyme-linked immunosorbent assay (ELISA), Western blot, and enzyme-linked immunoelectrotransfer blot (EITB). 24,25 In the review, it was concluded that surgery was the main modality of treatment (n ¼ 29), while 16 patients were managed medically with anticysticercal agents (albendazole, praziquantel). One of the patients refused any treatment.…”
Section: Review Of Literature and Resultsmentioning
confidence: 99%
“…presented an interesting case with “Intramedullary Cysticercosis (ICC) without Neurological Deficit.”[ 1 ] Ranjan et al . mentioned that “to best of our knowledge, this is the first case of ICC without neurological involvement.”[ 1 ] We agree that the case is rare, but we do not agree with this conclusion, and the problem might be due to a good literature review. We would like to take the note that there are already some publications on ICC without neurological complication.…”
mentioning
confidence: 99%